A Credit Assessment Model for Small Businesses in Egypt - Abdelsalam, Hisham M. E. (Indian Journal of Finance, 2008)
This papers aims to develop an assessment method to Credit Managers in order to assist them in evaluating the creditability of small business in Egypt. The proposed model needs to rely not only on financial indicators used in most common credit assessment models, but also on non-financial factors that are relevant to the structure of the Egyptian and other small economies. The model, thus, fits the nature of growing economies.